Análise da instabilidade harmônica em complexos eólicos com aerogeradores do tipo DFIG: Fundamentação, modelagem e mitigação - Troncha, Giordanni da Silva (2024)
Electrical power systems have been undergoing drastic changes with regard to a series of factors that influence their conventional operating pattern. This is mainly due to a worldwide call for sustainable policies, as well as the popularization and reduction in the cost of technologies that use semiconductors. In this sense, there is currently a massive integration of centralized renewable energy sources with non-linear characteristics, distributed generation units (DGs) and non-linear loads, such as electric vehicles and motor speed controllers. In this context, as new technologies in the energy sector become more mature and new resources are gradually developed, a diversity of types of energy generation sources are being incorporated into modern electrical grids, becoming a significant portion of the country's energy matrix. The significant increase in global energy demand in the last decade, as well as growing concerns about global warming, have led to processes of searching for alternative technologies to traditional ones, in order to move towards an energy supply focused on the decarbonization of the electricity sector. This, in turn, causes a change in the paradigms of electricity generation and consumption and, consequently, stimulates an energy transition. In view of these considerations, this thesis has proposed to clarify the conceptual differences of harmonic emission phenomena, in addition to proposing a detailed bibliographic review of the main methods of modeling wind systems, focusing on strategies in the time domain. To this end, three different wind turbine models were implemented in the ATPDraw® simulator. In addition, after the computational evaluation, a practical investigation of strategies for analyzing these phenomena was carried out, using the computational tools discussed and measurements performed in the field. Subsequently, methods for mitigating such events were proposed, considering not only the technical effectiveness, but also the cost-benefit of the application.